Komunikasi Semiotika Karya Seni Patung Monyet Di Sanna Ubud A Pramana Experience - Astrid Harikaputri; Ni Made Yuliani; I Ketut Wardana Yasa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2025)
This research employs a qualitative methodology with a semiotic approach to analyze the symbolic and communicative dimensions of sculpture as a form of visual language. Data were collected through observation, in-depth interviews with the designer, and documentation of the artwork and its surrounding context. The research focuses on the monkey sculpture at Sanna Ubud A Pramana Experience, a piece inspired by the story of Ni Diah Tantri, deeply rooted in Balinese cultural narratives. By applying the semiotic theories of Charles Sanders Peirce, Roland Barthes, and Ferdinand de Saussure, the study reveals that the sculpture functions as a layered communicative artifact that fulfills the criteria of icon, index, and symbol. Although physically static and three-dimensional, the sculpture operates as an effective one-way communication medium that persuasively conveys cultural and philosophical messages. The semiotic communication function of the sculpture not only transmits information about local cultural values but also creates interpretative space that engages the audience cognitively and affectively through denotative, connotative, and mythological meanings. Theoretically, this research offers a significant contribution to the development of communication science, particularly by expanding the scope of semiotic studies into the domain of three-dimensional visual arts. The findings demonstrate that sculpture can serve as an effective agent of cultural communication, as well as a medium of expression capable of bridging tradition, contemporary symbolism, and audience reception. Thus, this study enriches scholarly discourse on how artworks function as instruments of communication that represent identity, values, and meaning construction within specific cultural contexts.